Antiviral Properties of the Natural Polyphenols Delphinidin and Epigallocatechin Gallate against the Flaviviruses West Nile Virus, Zika Virus, and Dengue Virus - Vázquez-Calvo, Ángela; Jiménez de Oya, Nereida; Martín-Acebes, Miguel A.; Garcia-Moruno, Emilia; Saiz, Juan-Carlos (Frontiers in Microbiology, 2017)
The Flavivirus genus contains important pathogens, such as West Nile virus (WNV), Zika virus (ZIKV) and dengue virus (DENV), which are enveloped plus-strand RNA viruses transmitted by mosquitoes and constitute a worrisome threat to global human and animal health. Currently no licensed drugs against them are available, being, thus, still necessary the search for effective antiviral molecules. In this line, a novel antiviral approach (economical, simple to use, and environmental friendly) is the use of natural compounds. Consequently, we have tested the antiviral potential of different polyphenols present in plants and natural products, such as wine and tea, against WNV, ZIKV, and DENV. So that, we assayed the effect of a panel of structurally related polyphenols [delphinidin (D), cyanidin (Cy), catechin (C), epicatechin (EC), epigallocatechin (EGC), and epigallocatechingallate (EGCG)] on WNV infection, and found that D and EGCG inhibited more effectively the virus production. Further analysis with both compounds indicated that they mainly affected the attachment and entry steps of the virus life cycle. Moreover, D and EGCG showed a direct effect on WNV particles exerting a virucidal effect. We showed a similar inhibition of viral production of these compounds on WNV variants that differed on acidic pH requirements for viral fusion, indicating that their antiviral activity against WNV is produced by a virucidal effect rather than by an inhibition of pH-dependent viral fusion. Both polyphenols also reduced the infectivity of ZIKV and DENV. Therefore, D and EGCG impair the infectivity in cell culture of these three medically relevant flaviviruses.